A practical model for outsourcing bank services: The application of game theory - Golzar, Jafar; Hakimpour, Hossein; Mahmoodzadeh Vashan, Mahdi; Basirat, Behrooz (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: Banks tend to outsource their services to focus on their main task: collecting deposits and directing them toward investment. This research aims to identify a model that facilitates handing over services to the private sector and covering the interests of both parties in a win-win situation.Method: In this study, 16 semi-structured interviews with experts from banks and payment service provider (PSP) companies were conducted to understand outsourcing strategies for card reader devices. Employing Strauss and Corbin's thematic analysis and game theory, the study identified key strategies and preferences, which were then modeled to resolve conflicts and derive joint interaction strategies. Over 4 million scenarios were calculated using Min-Max strategy, and strategies for both parties were suggested based on Nash equilibrium results.Results: The qualitative data analysis resulted in identifying 22 strategies based on service marketing mix for parties and placing them in related groups (product, price, promotion, place, people, process, and physical evidence). The results of game theory and the balance point suggest the following strategies to the bank: diversity, quality, the latest device model, average account, number of agents, technical expertise, equipped workshop, and support equipment. The suggestion for the payment service provider (PSP) companies include brand, rent, transaction fee, discount, response hours, raffle, gifts, special privileges, appropriate treatment, type of cooperation, timely delivery, response speed, communication system, and location.Conclusion: The final outcome suggested specific strategies for banks and PSP companies to focus on, based on the Nash equilibrium and other game theory results. These strategies included diversification, quality, device up-to-datedness, technical expertise, equipped workshop, support equipment for banks, and brand, rent, transaction fees, response hours, lottery, gifts, special privileges, timely delivery, response speed, communication system, and location for PSP companies.